THE USE OF TRANSITIONS IN THE STUDENTS ARGUMENTATIVE ESSAY - Rachmawati, Suzana Meylita; Susanti, Yunik (English Education:Journal of English Teaching and Research, 2016)
One of academic writing assignment is argumentative essay. A way to make a coherent paragraph is using transitions which should be clearly and demonstrated in an argumentative essay. Transitions can be words and/or phrases that connect the idea in one sentence with the idea in another sentence. By using transitions, the wriring can be read smoothly. The purposes in conducting the study are to know and describe the use of transitions in student’s writing argumentative essay and the awareness of the students about using transitions. This is a qualitative research-content analysis. The subject of the research is the third grade students of English Department in academic year 2015/2016. There were 23 students: 3 good students, 17 average students, and 3 poor students. The instruments are documents, interview, and student’s journal. After collecting the data, the next step is analyzing them by using coding system, tabulation, and describing them. The results of this research are 1) almost all good students used transitions in essay correctly although there were few incorrect usages, then the average students and poor students had more corrections because they put the transitions in the wrong place, chose inappropriate transitions, used wrong grammatical, and over-use transitions, 2) All students in each category had good knowledge about the transitions, such as its definition, its types, and its function, how importance using transitions are. But sometimes they still felt difficult to use transitions. In conclusion, most of students in every category used transitions correctly even though there were some corrections, then the third grade students of English Department were conscious of transition signals, but they need more practice to apply it in the sentences in order to make their writing had better quality, easier to read and more understandable. Key Words : Argumentative Essay, Transitions